Anomalous polarization switching and permanent retention in a ferroelectric ionic conductor. Issue 1 (20th September 2019) - Zhou, Shuang; You, Lu; Chaturvedi, Apoorva; Morris, Samuel A.; Herrin, Jason S.; Zhang, Na; Abdelsamie, Amr; Hu, Yuzhong; Chen, Jieqiong; Zhou, Yang; Dong, Shuai; Wang, Junling
Abstract : Ionic conduction in a ferroelectric leads to anomalous polarization switching kinetics but prevents retention failure. Abstract : Ferroelectricity features the electrical switching of off-centered ions between the potential double well of the non-centrosymmetric lattice, while ionic conduction requires long-range hopping of ions across the lattice periodic potentials. The two seemingly mutually exclusive phenomena become strongly intertwined at the nanoscale in electrochemically active materials. However, the intrinsic coupling between ferroelectric switching and ionic activities in bulk crystalline materials remains largely unexplored. Here, we report anomalous polarization switching characteristics of a van der Waals (vdW) layered ferroelectric ionic conductor, CuInP2 S6 . By synergistic polarization switching and dielectric spectroscopy studies in both temperature and frequency domains, we reveal that the polarization switching kinetics of this compound is ionic-conduction-limited, due to the strong electrostatic interaction between ferroelectric and ionic defect dipoles. The crucial role of thermally-activated displacive instability of Cu ions is confirmed by the single-crystal X-ray crystallography results. The findings provide fundamental insight into the ionic kinetics under an electric field in crystals with coexisting dipole order (ferroelectricity) and disorder (ionic defect and conductivity). Last but not least, we demonstrate that the spontaneous ionic defect-polarization interlock can lead to permanent ferroelectric retention, which is essential for information storage.